Dimensionamento de um vaso separador trifásico horizontal para uma FPSO no pré-sal da Bacia de Santos: aplicação de um modelo semiempírico - Ferreira Alves , Adrielle; Komesu, Andrea (Latin American Journal of Energy Research, 2025)
With the advancement of exploration technologies in pre-salt fields and the increasing demand for petroleum derivatives, oil processing and refining stages have become increasingly relevant. Crude oil is typically found as a heterogeneous oily mixture, requiring separation and refining processes to obtain high-value-added byproducts. In primary processing, separator vessels play a crucial role in phase separation of the inlet stream and can be classified according to their orientation (vertical or horizontal) and the number of separated phases (two-phase or three-phase). The choice of configuration depends on the characteristics of the feed stream to be processed. In this context, this study aimed to implement a semi-empirical model for sizing a horizontal three-phase separator vessel in an FPSO located in the pre-salt of the Santos Basin. After a literature review, the sizing model proposed by Stewart and Arnold (2008) was adopted. In this model, the vessel dimensions are directly related to operational conditions and the physicochemical properties of the fluids. Consequently, any changes in these parameters can significantly impact the estimated geometry of the equipment. The results obtained using this model allowed for the determination of dimensions close to actual values. It is noteworthy that the correct sizing of this equipment is essential to ensure the efficiency of fluid phase separation and the proper classification of the feed for subsequent processes. Finally, given the applicability of the model and the relevance of the topic, the use of algorithms to automate calculations—along with the sizing of nozzles (inlet and outlet) and elliptical heads, as well as the definition of internal devices—would contribute to increasing the accuracy of results and providing greater flexibility in simulating different geometries.